1998
DOI: 10.1136/sti.74.4.253
|View full text |Cite
|
Sign up to set email alerts
|

What about money? Effect of small monetary incentives on enrollment, retention, and motivation to change behaviour in an HIV/STD prevention counselling intervention. The Project RESPECT Study Group.

Abstract: Objectives:We studied the eVect of small monetary incentives and non-monetary incentives of similar value on enrolment and participation in clinic based HIV/STD prevention counselling. We examined incident STDs to try to assess whether participants oVered money may be less motivated to change risky behaviours than those oVered other incentives. Methods: Patients from five US STD clinics were invited to enrol in a multisession risk reduction counselling intervention and, based on their enrolment date, were oVer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 3 publications
2
36
0
Order By: Relevance
“…A detailed description of subject selection and intervention procedures followed in the Project RESPECT randomized clinical trial appears elsewhere (Kamb et al, 1998a;Kamb et al, 1998b). In the present study, data from a subset of RESPECT subjects assigned to the Enhanced Counseling (n = 1,438), Brief Counseling, (n = 1,447), and Didactic Message (n = 1,443) conditions were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of subject selection and intervention procedures followed in the Project RESPECT randomized clinical trial appears elsewhere (Kamb et al, 1998a;Kamb et al, 1998b). In the present study, data from a subset of RESPECT subjects assigned to the Enhanced Counseling (n = 1,438), Brief Counseling, (n = 1,447), and Didactic Message (n = 1,443) conditions were analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…For example, colleagues (1997, 2000) demonstrated that client incentives almost doubled rates of treatment completion and improved abstinence over 27 months of follow up among cocaine-dependent clients. In the general medical literature, a study of an HIV/STD counseling intervention (Kamb et al, 1998) found that small monetary incentives paid to clients were more effective than non-monetary incentives of similar value on enrollment and treatment completion rates, but had no effect on post-enrollment STD rates.…”
Section: Inadequacy Of Previous Approaches To Retentionmentioning
confidence: 97%
“…Kamb et al (1998) found that payments motivated participation in interventions. Participants who attended the Week 1 session were more likely to attend the later sessions, indicating the importance of early contact.…”
Section: Discussionmentioning
confidence: 98%